Constituindo-nos professores no contexto da pandemia: Experiências de pibidianos egressos e de uma supervisora do PIBID - Freitas, Fabiana Ferreira (2024)
When considering the changes caused by the Covid-19 pandemic, the devastating impact on the education sector from 2020 onwards, the reconfiguration stipulated by the government to resume school activities through Emergency Remote Educational Activities, the present work aims to present as research results the contributions to investigations on how emergency remote teaching affected supervising and training teachers of the Pibid Subprojects and to discuss the implications of this new format for the initial training process of future teachers. This master's research aims to narratively understand teaching experiences lived by two teachers in training and a supervising teacher in the English/Spanish Pibid subproject in the pandemic period from October 2020 to April 2022. The specific objectives were to discuss the stories of two former participants in relation to the activities developed remotely in the Pibid English/Spanish project and to narrate and discuss my stories as a supervising teacher of Pibid in the pandemic period. In an attempt to understand and study more about these implications, I propose a study through the theoretical-methodological path according to Clandinin and Connelly (2000; 2011). To compose the field texts, I use narratives of two former Pibidians and my own narratives and I compose meanings of these narratives following the proposal of Ely, Vinz, Downing and Anzul (2001). I chose to develop this study in the state public school where I have been working for eight years with High School. Three people participated in this research: two students who graduated from Pibid, and me, the research teacher and English language teacher. I understand that the experiences narrated can help me understand important aspects of the experiences lived by me and the Pibid participants during the pandemic period. For a broader understanding of the context, I discuss some initial notions about Pibid, present Pibid, its actors and their roles within the program, Pibid and the pandemic context and some information about Pibid in English. At the end of the research, I understood that the experiences narrated could help me understand important aspects of the experiences lived by me and by the Pibid participants during the pandemic period.